Implementasi Model Pembelajaran Interaktif Dalam Manajemen Kelas Tahfidz (Studi Kasus IPA Tahfidz MA Nurul Jadid) - Muhammad Fadali Amar; Durrotul Masruroh (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2026)
This research applies an interactive learning model to the management of tahfidz classes at MA Nurul Jadid to improve students' ability to read and memorize the Al-Qur'an. The tahfidz process begins with coaching to equalize the basic abilities of the students, followed by memorization under the guidance of the ustadz and memorizing murojaah. Students are given the freedom to memorize outside the specified time and place. This research uses a qualitative method with a case study approach, data collection through interviews and documentation. Supporting and inhibiting factors for the tahfidz process include the students' goals and interests, intelligence, environment, and laziness. The research results show that the application of the interactive learning model in the management of tahfidz classes at MA Nurul Jadid follows a predetermined schedule. The Al-Qur'an tahfidz method used at MA Nurul Jadid is quite effective even though there are still several supporting and inhibiting factors in the tahfidz learning process. However, the results achieved by students are quite good and in accordance with the programmed curriculum.